Perception of orthodontists regarding the management of root resorption - clinical and legal aspects - Luíza Valéria de Abreu Maia; Renata de Castro Martins; Mariana Mourão de Azevedo Flores Pereira; Maurício de Almeida Cardoso; Leopoldino Capelozza Filho; Luiz Renato Paranhos (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the management adopted by orthodontists regarding root resorption caused by orthodontic treatment, relating it to their time of experience and the applicable legal norms. Methods: the study population consisted of 56 orthodontists from the city of Belo Horizonte (Minas Gerais State), and the tool to collect the data was a questionnaire with open and closed questions. Data were subjected to descriptive analysis. The association between the variables was analyzed by the chi-square test with significance level of 5%. Results: 57.6% of professionals temporarily interrupt the treatment; in the prevention and/or control, most professionals (80.4%) perform initial and periodical radiographs (every six months). Among the professionals with less than 5 years of experience as a specialist, 88.9% usually make periodic radiographic control; 100% affirmed to file the documents. No significant difference was found between dentists with different times of experience regarding the practice of archiving the documents (p = 0.271). Among those with 5-15 years of experience, 77.4% perform periodic radiographic control and 45.2% had already detected root resorption. Among those with more than 15 years of experience, 71.4% usually perform the periodic radiographic control, and 85.7% had already faced some case of root resorption in the clinical practice. Conclusions: Although most orthodontists adopt a correct management facing the occurrence, prevention and control of root resorption associated with orthodontic treatment, the majority are unaware about existing legislation in our country